Injection of Pseudomonas aeruginosa Exo toxins into host cells can be modulated by host factors at the level of translocon assembly and/or activity. - Julien Verove (Public Library of Science (PLoS), 2012)
Pseudomonas aeruginosa type III secretion apparatus exports and translocates four exotoxins into the cytoplasm of the host cell. The translocation requires two hydrophobic bacterial proteins, PopB and PopD, that are found associated with host cell membranes following infection. In this work we examined the influence of host cell elements on exotoxin translocation efficiency. We developed a quantitative flow cytometry based assay of translocation that used protein fusions between either ExoS or ExoY and the ß-lactamase reporter enzyme. In parallel, association of translocon proteins with host plasma membranes was evaluated by immunodetection of PopB/D following sucrose gradient fractionation of membranes. A pro-myelocytic cell line (HL-60) and a pro-monocytic cell line (U937) were found resistant to toxin injection even though PopB/D associated with host cell plasma membranes. Differentiation of these cells to either macrophage- or neutrophil-like cell lines resulted in injection-sensitive phenotype without significantly changing the level of membrane-inserted translocon proteins. As previous in vitro studies have indicated that the lysis of liposomes by PopB and PopD requires both cholesterol and phosphatidyl-serine, we first examined the role of cholesterol in translocation efficiency. Treatment of sensitive HL-60 cells with methyl-ß-cyclodextrine, a cholesterol-depleting agent, resulted in a diminished injection of ExoS-Bla. Moreover, the PopB translocator was found in the membrane fraction, obtained from sucrose-gradient purifications, containing the lipid-raft marker flotillin. Examination of components of signalling pathways influencing the toxin injection was further assayed through a pharmacological approach. A systematic detection of translocon proteins within host membranes showed that, in addition to membrane composition, some general signalling pathways involved in actin polymerization may be critical for the formation of a functional pore. In conclusion, we provide new insights in regulation of translocation process and suggest possible cross-talks between eukaryotic cell and the pathogen at the level of exotoxin translocation.